2020
DOI: 10.3390/antiox9111101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular-Genetic Insights into the Role of Oxidative Stress in Diabetic Retinopathy: Antioxidant Strategies and Future Avenues

Abstract: Reactive oxygen species (ROS) overproduction and ROS-signaling pathways activation attack the eyes. We evaluated the oxidative stress (OS) and the effects of a daily, core nutritional supplement regimen containing antioxidants and omega 3 fatty acids (A/ω3) in type 2 diabetics (T2DM). A case-control study was carried out in 480 participants [287 T2DM patients with (+)/without (−) diabetic retinopathy (DR) and 193 healthy controls (CG)], randomly assigned to a daily pill of A/ω3. Periodic evaluation through 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…After reviewing the abstracts of the 125 initial results by two different researchers, 15 studies were finally included: one case-control observational study [ 145 ] and 14 RCTs [ 129 , 144 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. The studies included are described in Table 3 .…”
Section: Role Of Oral Antioxidant Supplementationmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing the abstracts of the 125 initial results by two different researchers, 15 studies were finally included: one case-control observational study [ 145 ] and 14 RCTs [ 129 , 144 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. The studies included are described in Table 3 .…”
Section: Role Of Oral Antioxidant Supplementationmentioning
confidence: 99%
“…Four studies analysed the influence of antioxidant supplementation on DR onset or the degree of DR progression [ 145 , 146 , 151 , 153 ]. Three of them found a significant delay in DR progression in patients receiving Nutrof Omega ® or grape seed proanthocyanidins extract (GSPE) supplementation, with follow-up periods of at least 12 months [ 145 , 146 , 151 ]. The group of Haritoglou et al examined the onset of DME, basing the diagnosis on a funduscopic evaluation according to the ETDRS criteria, as an OCT device was not available at all the centres.…”
Section: Role Of Oral Antioxidant Supplementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrition and nutritional control have been suggested as potential interventions for slowing the progression of several diseases, such as ocular surface dysfunction dry eyes (OSD), glaucoma, diabetic retinopathy (DR), or age-related macular degeneration (AMD), much of these with controversial results [ 16 , 17 , 18 , 19 , 20 , 21 ]. It has been shown that docosahexaenoic acid (DHA), an omega-3 polyunsaturated fatty acid (ω3 PUFA), and its anti-inflammatory derivatives (series-3 prostaglandins, resolvin D1, neuroprotectin D1, maresin, etc.)…”
Section: Introductionmentioning
confidence: 99%